Econometric Analysis of Policy Choices for an Open Economy - Helliwell, John F.; Officer, Lawrence H.; Shapiro, Harold T.; Stewart, Ian A. (The Review of Economics and Statistics, 1969)
John F. Helliwell, Lawrence H. Officer, Harold T. Shapiro, Ian A. Stewart, Econometric Analysis of Policy Choices for an Open Economy, The Review of Economics and Statistics, Vol. 51, No. 4 (Nov., 1969), pp. 383-398